Proceedings of the Third Italian Conference on Computational Linguistics CLiC-it 2016 : 5-6 December 2016, Napoli - Giovanni Semeraro
The annual conference CLIC-it (''Italian Conference on Computational Linguistics'') is an initiative of the ''Italian Association of Computational Linguistics'' (AILC - www.ai-lc.it) which is intended to meet the need for a national and international forum for the promotion and dissemination of high-level original research in the field of Computational Linguistics (CL), with particular emphasis on Italian. The volume gathers the Proceedings of the ''Third Italian Conference on Computational Linguistics'' (CLiC-it 2016), held in Naples on 5-6 December 2016. The CLiC-it 2016 papers cover a wide range of topics in the area of computational linguistics and natural language (both written and spoken) processing, by targeting state-of-art theoretical results, experimental methodologies, technologies and application perspectives, and by addressing challenges, open issues and new perspectives related to current and novel trends of the discipline.